The Madrasah Principal's Strategy in Innovation of Learning Program to Build Students' Competence - Mohammad Abu Khoir; Muhammad Mujtaba Mitra Zuana (LP3M STIT Al Urwatul Wutsqo Jombang, 2021)
One of the efforts to respond to the challenges of the era, the principal of madrasah must be able to carry out its function as an innovator. In carrying out the role as an innovator, the madrasah principal acts as someone who makes educational innovations (renewals) considered monotonous and conventional. Therefore, by conducting innovation, the quality of educational atmosphere will be created which is able to adapt to the times. The study aims to describe and analyze the strategy of the principal of madrasah in the innovation of learning programs at MI Nurul Ulum Prambon and the innovation of learning programs in building students’ competence at MI Nurul Ulum Prambon. It used descriptive qualitative research, collecting data by observation, interviews, and documentation. The results of the study are: 1) The innovation of the learning program carried out at MI Nurul Ulum Prambon Sidoarjo consists of general programs and special programs 2) Innovation of learning programs to build students’ competence at MI Nurul Ulum Prambon is realized in students’ activities in schools through general programs and specifically carried out in the form of intracurricular activities, co-curricular activities, and extra-curricular activities.